The Poet as a Cultural Ambassador and Social Critic - Idowu James Adekunle (Randwick International of Social Science Journal, 2023)
Poetry is oral literature with aesthetic skills. It is a performative form of a cultural infusion of traditional and contemporary realities of the human world. Poetry in its true nature is political, economic, and sociological. Poetry is largely human. Previous studies have examined poetry as entertainment and poetic orature to neglect cultural significance and social criticism. Therefore, this study examines as poetry an embodiment of cultural identities and an element of social criticism. The anthology of Femi Abodunrin, entitled “It Would Take Time: Conversation with Living Ancestors” would be examined. This is in a bid to see how a poet serves as a cultural ambassador of his/her country and, at the same time, a social critic. Femi Abodunrin is a Nigerian-born poet. Schechner's Performance, Freudian, and Jungian psychoanalytic theories were used to analyze the selected collections. The selected poems are subjected to performance and literary analyses.